PENERAPAN PENDEKATAN CULTURALLY RESPONSIVE TEACHING (CRT) MELALUI MEDIA POP UP BOOK BERBASIS BUDAYA SUMATERA UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS II SD PADA MATERI KEBHINNEKAAN: Penelitian Tindakan Kelas - Nervalina Simalango; Indra Maryanti; Zuraida Hanum Lubis (STKIP Subang, 2025)
This study aims to improve the learning outcomes of second-grade elementary school students on the topic of diversity through the application of Culturally Responsive Teaching (CRT) combined with a Sumateran culture-based pop-up book. This is a Classroom Action Research (CAR) conducted in two cycles using the Kemmis and McTaggart model, including planning, action, observation, and reflection phases. Data were collected through observation, learning outcome tests, and documentation. The results showed that CRT enhances the relevance of learning by connecting with students' cultural backgrounds, thereby increasing motivation, participation, and conceptual understanding of diversity. In the first cycle, the students' average score rose to 80.96 with a mastery rate of 60.71%. After refinement in the second cycle, the average score reached 93.04 with a 100% mastery rate. These findings indicate that integrating local cultural values through contextual and interactive media such as pop-up books can strengthen students' understanding of tolerance and diversity, while also fostering an inclusive and meaningful learning environment.